The differential impact of COVID-19 on mental health: Implications of ethnicity, sexual orientation, and disability status in the United States - Brooks, Jordan M.; Patton, Cyrano; Maroukel, Sharon; Perez, Amy M.; Levanda, Liya (Frontiers in Psychology, 2022)
The COVID-19 pandemic’s effects on mental health interact with pre-existing health risks and disparities to impact varying populations differently. The present study explored the relationship between demographic variables (e.g. ethnicity, sexual orientation, and disability status), distress and mental health (e.g. depression, anxiety, somatic complaints, and pandemic distress), and vulnerability factors for COVID-19 (e.g. personal health vulnerabilities, community members’ health vulnerabilities, and environmental exposure risks at work or home). An online cross-sectional study was conducted from June 18th to July 17th 2020, reflecting the impact of early phase COVID-19 pandemic and related shelter-in-place measures in the United States. Participants were adults residing in the United States (N = 594), with substantial subsamples (N ≥ 70) of American Indian, Asian American, African American, and Hispanic and/or Latinx participants, as well as people with disabilities and sexual minorities. Outcomes measured were depression, hopelessness, somatic complaints, anxiety-related disorders, locus of control, and a novel measure of pandemic-related distress. Data were analyzed using ANCOVA, χ² test, and correlation coefficients. Generally, younger individuals, and those with less financial power –across all identities– suffered more distress. When controlling for age, lower financial power was associated with higher scores on the Center for Epidemiologic Studies Depression Scale-Revised (CESD-R; r = -.21, p = < .001), Beck Hopelessness Scale (BHS; r = -.17, p < .001), Patient Health Questionnaire-15 (PHQ-15; r = -.09, p = .01), Screen for Child Anxiety Related Emotional Disorders for Adults Panic Disorder (SCARED-A PD; r = -.14, p < .001), SCARED-A generalized anxiety disorder (GAD; r = -.13, p = .002), SCARED-A obsessive-compulsive disorder (OCD; r = -.08, p = .04), and the COVID-19 Pandemic Distress restriction/disconnection scale (C19PDS; r = -.10, p = .009). Additionally, disparities were found, in general, for marginalized identities by gender, sexual orientation, and disability status. Importantly, each ethnicity subsample showed a unique pattern of relationships between COVID-19 risk variables and mental health symptoms. Results support the hypothesis that any pandemic may amplify preexisting social and financial disparities. Overall, interventions at the clinical, governmental, or health equity level should take into consideration the needs of vulnerable groups.